2021
DOI: 10.1101/2021.11.30.470579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human ventromedial prefrontal cortex lesions enhance expectation-related pain modulation

Abstract: Pain is strongly modulated by expectations and beliefs. Research across species indicates that subregions of the ventromedial prefrontal cortex (VMPFC) play a fundamental role in learning and generating predictions about valued outcomes. Consistent with this overarching framework, neuroimaging studies of experimental pain indicate that VMPFC activation tracks expectations of pain relief and statistically mediates expectation-related reductions in responses to painful stimuli across a distributed pain processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…suppression) we observed is consistent with this modulation or down-regulation: Individuals who showed greater activation of these regions in response to high pain cues showed stronger negative associations between brain activation and subjective pain, controlling for cue. Identifying factors that predict individual differences in brain mediators is an important direction for future research, as is testing the causal contributions of these modulatory regions to placebo analgesia and expectancy-based pain modulation through interventions such as transcranial magnetic stimulation ( Krummenacher et al, 2010 ) or in individuals with neurosurgical lesions ( Motzkin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…suppression) we observed is consistent with this modulation or down-regulation: Individuals who showed greater activation of these regions in response to high pain cues showed stronger negative associations between brain activation and subjective pain, controlling for cue. Identifying factors that predict individual differences in brain mediators is an important direction for future research, as is testing the causal contributions of these modulatory regions to placebo analgesia and expectancy-based pain modulation through interventions such as transcranial magnetic stimulation ( Krummenacher et al, 2010 ) or in individuals with neurosurgical lesions ( Motzkin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lateral OFC is thought to evaluate value of independent options, whereas medial OFC and VMPFC have been linked to value-based choice for the purpose of comparison ( Rudebeck and Murray, 2014 ). We recently showed that surgical lesions of the bilateral VMPFC enhance instructed cue effects on pain in a stable environment ( Motzkin et al, 2021 ). Additional studies that use lesion symptom mapping in heterogeneous frontal samples or measure aversive learning in nonhuman primates can provide further insights on the contribution of different portions of the VMPFC/OFC to pain modulation and instructed learning.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that these connectivity differences may contribute to the NAc activity that distinguishes the two groups [ 64 ]. The vmPFC may play a role in representing the affective and motivational qualities of pain that contribute to its strong aversive drive and was found as a critical link between cognitive state and the affective-motivational features of pain [ 67 ]. Yet, no significant differences were found in the connectivity of this region between our groups.…”
Section: Discussionmentioning
confidence: 99%
“…We recently evaluated the contribution of the VMPFC, a region implicated in flexible learning and value-based decision making (Murray et al 2007;Roy et al 2012;Schneider & Koenigs 2017;Schoenbaum et al 2007). We compared pain and its modulation by expectation in individuals bilateral VMPFC lesions following surgical resection to healthy controls with intact brains (Motzkin et al 2021). Groups did not differ in pain sensitivity or the correspondence between pain and autonomic activity, but individuals with VMPFC lesions reported stronger cue-based pain modulation and larger differences in expectations, providing evidence that VMPFC is not necessary for the development of expectations.…”
Section: How Learning Impacts Subjective Pain Studies Of Pavlovian An...mentioning
confidence: 97%